Analisis Biaya Produksi Penambangan Batu Gamping Pada PT. Diamond Alfa Propertindo Kabupaten Buton Tengah Provinsi Sulawesi Tenggara - Ardian Andani; Hasriyanti Hasriyanti; Isramyano Yatjong (Program Studi Teknik Pertambangan, Fakultas Teknik, Universitas Sulawesi Tenggara, 2025)
The research was conducted at PT. Diamond Alfa Propertindo in Central Buton Regency in the Gundu-Gundu village area with a land area of approximately 4,905 hectares. This study aims to analyze the production costs of limestone mining using descriptive quantitative methods through an analysis of the amount of explosives, data on the cost of explosives, data on fuel costs, data on operator costs, the number of mechanical tools, and the costs of crusher and workshop employees. The results of the study show the production costs of limestone mining incurred by PT. Diamond Alfa Propertindo in January 2025. The cost of drilling activities for 7 days in January 2025 was IDR 20,300,000, while the cost of blasting activities for 7 days in January 2025 was IDR 357,184,070. The costs incurred by PT. Diamond Alfa Propertindo for excavation activities during January 2025 amounted to IDR 168,000,000. The costs incurred by PT. Diamond Alfa Propertindo for loading activities during January 2025 amounted to IDR 168,000,000. The cost of transporting limestone incurred during January 2025 amounted to IDR 144,000,000. The total cost incurred in January 2025 amounted to IDR 234,000,000. The cost of 13 crusher employees in January 2025 was IDR 39,000,000. In January 2025, the cost of 17 workshop employees was 51,000,000. Therefore, the total cost of limestone mining production activities at PT. Diamod Alfa Propertindo in January 2025 was 1,181,484,070.